Megarthrus of China. Part 3. Comments on the occurrence of Megarthrus nitidulus Kraatz, 1857 in China, and description of a new species, with notes on teratology and phoretic acari in the genus (Coleoptera: Staphylinidae: Proteininae) - Zhang, Shan; Cuccodoro, Giulio; Chen, Li; Liu, Zhiping (Zootaxa, 2021)
A new species, Megarthrus heise Zhang, Cuccodoro, Chen & Liu sp. nov., resembling Megarthrus nitidulus Kraatz, 1857 is described from Qinghai, Sichuan, Gansu, Shaanxi, Shanxi provinces and Beijing in China. The record of M. nitidulus in China was apparently based on a misidentification, and the species is thus removed from the list of Chinese Megarthrus. Phoresy of acari and teratological modification of the abdomen are also reported for the first time in the genus.